Ações afirmativas: a igualdade e o acesso pleno à educação superior dos grupos sociais historicamente excluídos - Lopes, Toni Ronei (2014)
This research aims to examine, from an interdisciplinary study that correlates Law, Education, Sociology, and other related areas, entry into the Federal University of Santa Maria through the Affirmative Action Program of Racial and Social Inclusion. Brazil has been noted historically for being a country where the socio-racial inequalities prevail, either by poor and inadequate income distribution, coupled with the absence of effective public policies, or even because of a discriminatory national culture. In addition to these findings, first, an approach will be made-by focusing on the right to education on the importance, impact and repercussions of International Human Rights Treaties incorporated into the Brazilian legislation. In a second stage, once situated the right to education in parental normative ordering, given the controversies established around the fundamentality of social rights in Brazil, will discuss up-while the humanitarian and democratic rule of law, based on the principle model of human dignity, of the effectiveness, concreteness and enforceability of these values in the face of the defaulting Government. Finally, in this scenario, neoconstitucionalista, will address about the Program Racial and Social inclusion adopted by the Federal University of Santa Maria, in order to reflect and evaluate, from the perspective of the principle of substantive equality, the core element of the decision Supreme Court which, in the judgment of action breach of fundamental precept paragraph nº.186-2/DF declared, in 2012, the constitutionality of the quota system in education, the documents that led to Resolution N. 011/07, which established in the Affirmative UFSM Program, aimed at the domestic level design perspective and concomitantly, demonstrating the positions of the Directors Council of Education Research and Extension, which best make compatible with the Brazilian socio-educational and constitutional order.